2005
DOI: 10.1002/humu.9376
|View full text |Cite
|
Sign up to set email alerts
|

Lafora progressive myoclonus epilepsy mutation database-EPM2A and NHLRC1 (EMP2B) genes

Abstract: Progressive Myoclonus Epilepsy (PME) of the Lafora type is an autosomal recessive disease, which presents in teenage years with myoclonia and generalized seizures leading to death within a decade of onset. It is characterized by pathognomonic inclusions, Lafora bodies (LB), in neurons and other cell types. Two genes causing Lafora disease (LD), EPM2A on chromosome 6q24 and NHLRC1 (EPM2B) on chromosome 6p22.3 have been identified, and our recent results indicate there is at least one other gene causing the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 22 publications
(28 reference statements)
0
44
0
Order By: Relevance
“…Mutations in malin account for more than 50% of reported cases of LD (30,31). Recently it was shown that malin and laforin recruited to aggresomes under proteasome impairment and the malin-laforin complex degrade misfolded proteins (21).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in malin account for more than 50% of reported cases of LD (30,31). Recently it was shown that malin and laforin recruited to aggresomes under proteasome impairment and the malin-laforin complex degrade misfolded proteins (21).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several groups have identified mutations in the EPM2A and NHLRC1 genes in LD families from diverse populations. Although a database for the LD mutations was reported in the literature [Ianzano et al, 2005] (http://projects.tcag.ca/lafora/), neither it is [Ganesh et al, 2003], R5 and EPM2AIP1 require the full-length laforin for interaction Ferná ndez-Sá nchez et al, Ianzano et al, 2003] (interacting domains identified by thin lines). Laforin-laforin and laforin-malin interactions (identified by double headed arrows) have also been reported [Dubey and Ganesh., 2008;Ferná ndez-Sá nchez et al, 2003;Gentry et al, 2005;Liu et al, 2006].…”
Section: Mutational Spectrum Of Epm2a and Nhlrc1 Genesmentioning
confidence: 99%
“…To date, mutations in two genes have been shown to account for ϳ90% of LD cases. Approximately 60% of LD cases can be attributed to mutations in the EPM2A (epilepsy progressive myoclonus type 2A) gene, which encodes, by sequence, a dual specificity protein phosphatase named laforin (12,15,16). Laforin also contains a highly conserved carbohydrate-binding module subtype 20 (17) that interacts with glycogen and the polyglucosan found in patients with LD (18,19).…”
mentioning
confidence: 99%